Sustainable. Libraries in the time of ecological crisis (notes in the margin of Going Green) - Giovanni Di Domenico (JLIS.it, 2020)
Going Green is a recent IFLA book, which contains an excellent review about what libraries are doing, in various parts of the world, to protect the environment and help their communities, all the collectivity, to face the ecological crisis. In addition, the reading of Going Green also allows us to reflect on implications that a green and sustainable option involves in the way of interpreting the social role of the libraries, inspiring their management policies, improving their perception within the public sphere, assessing their impact. This article aims to frame and discuss the contents of the book in the light of conceptual and practical developments of the Green Library Movement. The latter tend now to entrench – in and with the libraries – a not only environmental, but also social, economic and cultural idea of sustainability.